Genes de referência para expressão gênica em codornas de corte - Macário, Maíse dos Santos (2016)
The production of common quail is on increasing development and needs further genetics studies for productive direction. As the PCR technique in real time the most important in the analysis of animal gene expression, studies and experiments related components are needed. Among these components is the reference gene, normalizer data that has great impact on the results and has direct influence on the success of the analysis, which must have significant expression in tissue and invariably in all the experimental conditions. Among the experimental conditions, sex (male and female) can be considered, since there are research about responses in the animal gene expression in both sexes. Thus it is necessary to use a single set of reference genes for normalizing expression data from both samples (male and female), by eliminating the effect of sex. So, We aim with this study was to evaluate the stability and recommend reference genes for quantitative real-time PCR in different quails tissues of both sexes. The stability of 10 housekeeping genes (GAPDH, RPL5, MRPS27, MRPS30, TFRC, HMBS, EEF1, LDHA, B2M and UBC) was analyzed in four tissues (heart, thigh, brain and spleen) of males and females quails, from online available RefFinder tool. The RefFinder is based on the results of programs and methods commonly used for this purpose (Bestkeeper, NormFinder, GeNorm and ΔCq method) and the analysis was done separately for each tissue. The results confirm prior knowledge that different tissues express different genes, that it was noted from the different recommendations for each tissue. However, it is important to note that although the sex be able to influence the expression of genes, we observed stable constitutive genes for both sexes. The most stable housekeeping genes were: MRPS30, EEF1 and HMBS in thigh muscle; B2M, GAPDH and UBC in brain; MRPS30, TFRC and HMBS in heart; and EEF1, LDHA and HMBS in spleen, It is therefore recommended to be used as reference genes for gene expression studies of male and female quails. The recommendation of stable genes that can be used in both sexes quail facilitates the execution of subsequent genetic studies needed to assess the animals eliminating the effect of sex, influencing, consequently, in the development on the entire production.